주파수 변화에 따른 5상 농형 유도전동기의 정수 추정 - 김민회(Min-Huei Kim) (전기학회 논문지 P권, 63(4), 2014)
This paper propose a variable parameter estimations of five-phase squirrel-cage induction motor(IM) for speed control system. In order to high performance control of AC motor using a field oriented control(FOC) and direct torque control(DTC) algorithm, there are required precise motor parameters for slip calculation, flux observer, controller gain, rotor position, speed estimation, and so on. We are suggest a analyzed estimation results of the motor parameters that developing five-phase squirrel-cage IM have a stator of concentrated winding for experimental of variable input power frequency. There are results of stator winding test, no-load test, locked-rotor test, variable actual load test, and estimated parameters of equivalent circuits using manufactured experimental apparatus by IEEE Standard Test Procedure for Polyphase Induction Motors and Generators 112-2004.